Метод эффективной обработки импульсно-модулированных сигналов - Serdjukov, Yu. P. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
A method for processing pulse-modulated signals is described, which ensures effective reduction of intersymbol interference. An estimate of the magnitude of intersymbol distortions is obtained, which can be used in the design of communication systems.